Protective effect of 4,4'-diaminodiphenylsulfone against paraquat-induced mouse lung injury - Cho, Sung Chun (Korean Society for Biochemistry and Molecular Biology, 2011)
Although 4,4'-diaminodiphenylsulfone (DDS, dapsone) has been used to treat several dermatologic conditions, including Hansen disease, for the past several decades, its mode of action has remained a topic of debate. We recently reported that DDS treatment significantly extends the lifespan of the nematode C. elegans by decreasing the generation of reactive oxygen species. Additionally, in in vitro experiments using non-phagocytic human fibroblasts, we found that DDS effectively counteracted the toxicity of paraquat (PQ). In the present study, we extended our work to test the protective effect of DDS against PQ in vivo using a mouse lung injury model. Oral administration of DDS to mice significantly attenuated the lung tissue damage caused by subsequent administration of PQ. Moreover, DDS reduced the local expression of mRNA transcripts encoding inflammation-related molecules, including endothelin-1 (ET-1), macrophage inflammatory protein-1α (MIP-1α), and transforming growth factor-β (TGF-β). In addition, DDS decreased the PQ-induced expression of NADPH oxidase mRNA and activation of protein kinase Cµ (PKCµ). DDS treatment also decreased the PQ-induced generation of superoxide anions in mouse lung fibroblasts. Taken together, these data suggest the novel efficacy of DDS as an effective protective agent against oxidative stress-induced tissue damages.